Ocean acidification research in the Mediterranean Sea: Status, trends and next steps - Hassoun, Abed El Rahman; Bantelman, Ashley; Canu, Donata; Comeau, Steeve; Galdies, Charles; Gattuso, Jean-Pierre; Giani, Michele; Grelaud, Michaël; Hendriks, Iris Eline; Ibello, Valeria; Idrissi, Mohammed; Krasakopoulou, Evangelia; et al. (Frontiers in Marine Science, 2022)
Ocean acidification (OA) is a serious consequence of climate change with complex organism-to-ecosystem effects that have been observed through field observations but are mainly derived from experimental studies. Although OA trends and the resulting biological impacts are likely exacerbated in the semi-enclosed and highly populated Mediterranean Sea, some fundamental knowledge gaps still exist. These gaps are at tributed to both the uneven capacity for OA research that exists between Mediterranean countries, as well as to the subtle and long-term biological, physical and chemical interactions that define OA impacts. In this paper, we systematically analyzed the different aspects of OA research in the Mediterranean region based on two sources: the United Nation’s International Atomic Energy Agency’s (IAEA) Ocean Acidification International Coordination Center (OA-ICC) database, and an extensive survey. Our analysis shows that 1) there is an uneven geographic capacity in OA research, and illustrates that both the Algero-Provencal and Ionian sub-basins are currently the least studied Mediterranean areas, 2) the carbonate system is still poorly quantified in coastal zones, and long-term time-series are still sparse across the Mediterranean Sea, which is a challenge for studying its variability and assessing coastal OA trends, 3) the most studied groups of organisms are autotrophs (algae, phanerogams, phytoplankton), mollusks, and corals, while microbes, small mollusks (mainly pteropods), and sponges are among the least studied, 4) there is an overall paucity in socio-economic, paleontological, and modeling studies in the Mediterranean Sea, and 5) in spite of general resource availability and the agreement for improved and coordinated OA governance, there is a lack of consistent OA policies in the Mediterranean Sea. In addition to highlighting the current status, trends and gaps of OA research, this work also provides recommendations, based on both our literature assessment and a survey that targeted the Mediterranean OA scientific community. In light of the ongoing 2021-2030 United Nations Decade of Ocean Science for Sustainable Development, this work might provide a guideline to close gaps of knowledge in the Mediterranean OA research. Systematic Review Registration https://www.oceandecade.org/